Discovery-based approach combined with active learning to improve student learning experiences for STEM students - Karan, Ebrahim (Ilmu Inovasi Nusantara, 2023)
A combination of discovery-based learning (as a novel instructional approach) and Pro-Con Grids (as an active learning activity) is used to improve long-term retention among STEM students. Students in a required Construction Management course were provided with a course lecture prior to in-class sessions. A quiz was used for each lecture to gain insight into students’ understanding and to evaluate the effectiveness of the learning method. During the in-class sessions, a blank sheet of paper was handed out to students to make a list of the pros and cons/advantages and disadvantages of the topics covered in the lecture. Once the pro-con grid was complete, the students were directed to share their documents with the instructor. This was followed by a summary of key concepts and then a review of the correct answers. Data was collected for this study in two forms; through a student survey and grades. The results showed that discovery-based learning could convince students to find and use information rather than memorizing and repeating concepts and facilitate effective group work. In addition, the grade comparisons for three semesters indicated that the higher the use of discovery learning during the course the higher the course grades were found to be